2002
DOI: 10.1097/00000539-200206000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Inhaling Nitrous Oxide or Xenon Does Not Influence Bowel Wall Energy Balance During Porcine Bowel Obstruction

Abstract: In anesthetized pigs, short-term inhalation of xenon or nitrous oxide over 4 h when compared with total IV anesthesia had no additional deleterious effects on the metabolic balance of the gut wall during intestinal obstruction, no matter whether the arterial blood flow was reduced or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…20 However, little is known about side-effects on regional perfusion and oxygenation, especially on intestinal oxygenation. [4][5][6] However, this is an important factor, because other anaesthetics, such as volatiles, induce intestinal hypoperfusion and impairment of mucosal oxygenation; [11][12][13] this must be avoided because mucosal hypoxia increases gut permeability and induces bacterial translocation. 9 Hence, the gut is a major factor contributing to the development of systemic inflammatory response syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, little is known about side-effects on regional perfusion and oxygenation, especially on intestinal oxygenation. [4][5][6] However, this is an important factor, because other anaesthetics, such as volatiles, induce intestinal hypoperfusion and impairment of mucosal oxygenation; [11][12][13] this must be avoided because mucosal hypoxia increases gut permeability and induces bacterial translocation. 9 Hence, the gut is a major factor contributing to the development of systemic inflammatory response syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, little is known about its effects on regional haemodynamics, especially effects on intestinal perfusion and oxygenation. [3][4][5][6] Recently the intestinal region has become the subject of growing interest because of its possible function in the development of systemic inflammatory response syndrome, sepsis and multiple organ failure. 4 5 Perioperative hypoperfusion 6 7 and impaired oxygenation of the gut, especially of the intestinal mucosa, are major factors contributing to secondary multi-organ dysfunction, and should be avoided.…”
mentioning
confidence: 99%
“…Previous studies have shown that increased IAP is a major role-player in the development of morbidity related to intestinal occlusion [ 6 ]. Most experimental studies on intestinal obstruction [ 13 18 ], have to date been conducted in rats, focusing on the evaluation of the effects of ischemic hypoperfusion and bacterial translocation. These studies simulated intestinal obstruction by restricting blood supply to the intestine using ligation at the level of the ileocaecal valve [ 13 , 15 18 ] or using materials to reduce the intestinal lumen [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ligation models: A simple ligation of the lumen at the desired level of obstruction has been a commonly cited technique since the beginning of the twentieth century [26][27][28][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] and is probably the most feasible and cost-effective model to produce an acute complete intestinal obstruction. The desired intestinal loop is identified after entering the abdominal cavity, and the adjacent mesentery is carefully dissected so as to create a small mesenteric window but not to damage the mesentery itself or the mesenteric marginal vessels.…”
Section: Complete Mechanical Obstructionmentioning
confidence: 99%
“…A suture ligation is passed around the intestinal lumen and tied. Silk sutures are most commonly used, but any type of suture material is acceptable [59]. This technique is easy to perform even from researchers with basic surgical experience.…”
Section: Complete Mechanical Obstructionmentioning
confidence: 99%